Analisis Produktivitas Alat Gali Muat Menggunakan Metode Overall Equipment Effectivenees Pada Kegiatan Pengupasan Lapisan Penutup Overburden Di Blok 3 PT. Antang Gunung Meratus, Kabupaten Tapin, Provinsi Kalimantan Selatan - Budi , Ganung Budi Prasetyo (Retii, 2024)
As a subsidiary of PT. Baramulti Sukses Sarana (BSSR), PT. Antang Gunung Meratus is a coalmine located in South Kalimantan, Indonesia. In 2004 the Indonesian government entered into ajoint agreement for coal mining business work (PKP2B). PT. Antang Gunung Meratus uses aKomatsu PC 2000-8 type excavator for the overburden loading process with a productivity targetfor the contractor of 860/hour per unit. The production target per unit in one month at the WarutePit is 549,000 BCM/month. Production on the PC 2000-8 excavator unit with unit number PC2008-X169 was 433,062 BCM/month. analyze the productivity of the loading digging equipmentobtained using actual calculations and the Overall Equipment Effectiveness (OEE) method, aswell as analyzing the factors that influence the productivity of the Komatsu PC 2000-8 loadingdigging equipment in overburden removal activities. The OEE method is used to analyze how toimprove equipment performance. include low time effective work and work efficiency and theplanned distribution time has not been achieved. Efforts that can be made to achieve productiontargets include increasing effective working time by reducing the time obstacles are avoided,optimizing tool work efficiency, training operator skills to support the circulation time of loadingand digging equipment and adding tools